Development and characterization of p1025-loaded bioadhesive liquid-crystalline system for the prevention of Streptococcus mutans biofilms - Calixto, Giovana Maria Fioramonti [UNESP]; Duque, Cristiane [UNESP]; Aida, Kelly Limi [UNESP]; dos Santos, Vanessa Rodrigues [UNESP]; Massunari, Loiane [UNESP]; Chorilli, Marlus [UNESP] (Taylor & Francis, 2017)
Formation of a dental biofilm by Streptococcus mutans can cause dental caries, and remains a costly health problem worldwide. Recently, there has been a growing interest in the use of peptidic drugs, such as peptide p1025, analogous to the fragments 1025–1044 of S. mutans cellular adhesin, responsible for the adhesion and formation of dental biofilm. However, peptides have physicochemical characteristics that may affect their biological action, limiting their clinical performance. Therefore, drug-delivery systems, such as a bioadhesive liquid-crystalline system (LCS), may be attractive strategies for peptide delivery. Potentiation of the action of LCS can be achieved with the use of bioadhesive polymers to prolong their residence on the teeth. In line with this, three formulations – polyoxypropylene-(5)-polyoxyethylene-(20)-cetyl alcohol, oleic acid, and Carbopol C974P in different combinations (F1C, F2C, and F3C) were developed to observe the influence of water in the LCS, with the aim of achieving in situ gelling in the oral environment. These formulations were assessed by polarized light microscopy, small-angle X-ray scattering, rheological analysis, and in vitro bioadhesion analysis. Then, p1025 and a control (chlorhexidine) were incorporated into the aqueous phase of the formulation (F + p1025 and F + chlorhexidine), to determine their antibiofilm effect and toxicity on epithelial cells. Polarized light microscopy and small-angle X-ray scattering showed that F1C and F2C were LCS, whereas F3C was a microemulsion. F1C and F2C showed pseudoplastic behavior and F3C Newtonian behavior. F1C showed the highest elastic and bioadhesive characteristics compared to other formulations. Antibiofilm effects were observed for F + p1025 when applied in the surface-bound salivary phase. The p1025-loaded nanostructured LCS presented limited cytotoxicity and effectively reduced S. mutans biofilm formation, and could be a promising p1025-delivery strategy to prevent the formation of S. mutans dental biofilm.
Keywords: Bacterium; Dental caries; Formulation; Liquid crystal; Peptide; Polymer